The Routledge history of American sexuality - Murphy, Kevin P., 1963-; Ruiz, Jason; Serlin, David (New York, NY : Routledge, 2020)
"The Routledge History of American Sexuality brings together contributions from leading scholars in history and related fields to provide a far-reaching but concrete history of sexuality in the United States. This interdisciplinary group of authors explore a wide variety of case studies and concepts to provide an innovative approach to the history of sexual practices and identities over several centuries. Each essay interrogates a provocative word or concept to reflect on the complex ideas, debates and differences of historical and cultural opinions surrounding it. Its authors challenge readers to look beyond contemporary identity-based movements in order to excavate the deeper histories of how people have sought sexual pleasure, power, and freedom in the Americas. This book is an invaluable resource for students or scholars seeking to grasp current research on the history of sexuality and is a seminal text for undergraduate and graduate courses on American history, Sexuality Studies, Women's Studies, Gender Studies, or LGBT Studies"--
16. Domesticity -- Sexual Constraint and Subjection within the Marital Household -- Sexual Surveillance and Intervention -- Alternative Domesticities -- Domestic Diversity and Normativity -- Notes -- 17. Empire -- Notes -- 18. Hygiene -- Establishing Infrastructures -- Segmenting Populations -- Managing Sexuality -- Mental Hygiene -- Hygiene and Sexuality since the 1960s -- Notes -- 19. Incarceration -- Sex and the Early Prison -- Prison Sexual Culture -- The Prison as Laboratory -- Sexuality and the Carceral State -- Notes -- 20. Marriage -- Defining a New Nation: Marriage as Civil Contract
OCLC-licensed vendor bibliographic record.
Keywords: Sex -- United States -- History; Sex customs -- United States -- History; HISTORY / United States / General; SOCIAL SCIENCE / Gender Studies